LEGAL PROTECTION OF THE NATIONAL OIL AND GAS ENERGY BY LAW NUMBER 22 OF 2001 - Bambang Heri Supriyanto, (International Journal of Social Science, 2023)
National Oil and Gas Energy for Indonesia so plays an important role in the field of oil and gas industry. Pertamina is the only State Oil and Gas Company submitted the task to manage all activities of the Indonesian Oil and Gas Energy from upstream to downstream and export activities, is the beginning of a political era of international cooperation in the upstream oil and gas activities with the use of system agreement Produktion Sharing Contract (kps). The purpose of this paper is the settlement of disputes in the mining oil and gas energy is by starting with the principles and definitions, basic law and the law of oil and gas resources that exist in Indonesia, as contained in Act No. 22 of 2001 and aspects of legal protection in the oil and gas energy mining system , and the settlement of disputes in the national oil and gas energy, namely; 1). court; 2). Alternative dispute resolution; view of Islamic law on mining energy as a result of the earth and the results of its use for the welfare of the people in line with the Islamic religion that results or benefits can be used for the welfare of the people